Development of the Desa Jago Literasi Digital Toolkit for Frontier, Remote, and Disadvantaged areas - Firman; Al Jumroh, Siti Fatihaturrahmah; S, Hendra (JTP - Jurnal Teknologi Pendidikan, 2025)
In today's digital era, technology plays a crucial role in bridging the gap in access to information and education, especially in Indonesia's 3T regions frontier, remote, and disadvantaged areas. However, limited infrastructure and inadequate access to appropriate tools remain persistent challenges. This study aims to develop the DJ LITA device as a practical solution for these communities and to ensure that the device meets the standards of validity, practicality, and effectiveness. The research applies a modified version of the Borg & Gall model combined with the Multimedia Development Life Cycle (MDLC), resulting in twelve development stages: research and data collection, concept development, design, material gathering, production, initial testing, product revision, field testing, operational revision, operational testing, final revision, and dissemination. A descriptive approach was used to analyze the development process, validator feedback, and trial outcomes. Due to the small and non-random sample, non-parametric statistical methods were applied to suit the data characteristics and research goals. Results from black box testing confirmed the device's technical validity, with no system errors detected. Practicality was supported by expert validation (87.5% very practical), and trials involving 25 participants in a small group and 30 in a large group, with an overall practicality score of 96.22%. The effectiveness of the DJ LITA  application was shown through a 63.38% average improvement in post-test scores compared to pre-tests, indicating a moderate level of effectiveness. This research provides a relevant and adaptive technological approach to improving information and education access in underserved regions.